2017
DOI: 10.1159/000481455
|View full text |Cite
|
Sign up to set email alerts
|

Are Inflammatory Cytokines Associated with Pain during Acute Myocardial Infarction?

Abstract: Objective: Pain and inflammation during acute myocardial infarction (AMI) have been associated with the development of posttraumatic stress disorder and may also impact negatively on somatic outcome. We investigated the relationship between pain during AMI and levels of circulating proinflammatory (tumor necrosis factor [TNF]-α, interleukin [IL]-6) and anti-inflammatory (IL-33 and tissue growth factor [TGF]-β1) cytokines. Methods: Data were collected as part of the Myocardial Infarction - Stress Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
0
1
Order By: Relevance
“…They found that a significantly higher proportion of patients with chronic low-back pain had increased TNF-α levels during a 6-month course compared to a healthy control group. Unlike in previous studies, Imholz et al (2017) found no significant association between chest pain and either TNF-α or IL-6 levels in patients with myocardial infarction. They suggested that during the period between symptom onset and blood collection, pro-inflammatory cytokines may have been downregulated by anti-inflammatory mediators, making any initial association between levels of these cytokines and pain intensity difficult to detect.…”
Section: Discussioncontrasting
confidence: 99%
“…They found that a significantly higher proportion of patients with chronic low-back pain had increased TNF-α levels during a 6-month course compared to a healthy control group. Unlike in previous studies, Imholz et al (2017) found no significant association between chest pain and either TNF-α or IL-6 levels in patients with myocardial infarction. They suggested that during the period between symptom onset and blood collection, pro-inflammatory cytokines may have been downregulated by anti-inflammatory mediators, making any initial association between levels of these cytokines and pain intensity difficult to detect.…”
Section: Discussioncontrasting
confidence: 99%